Enhanced solar light photocatalytic degradation of tetracycline by aero-GaN and ZnO microtetrapods functionalized with noble metal nanodots - Vladimir Ciobanu; Tatiana Galatonova; Pavel Urbanek; Tudor Braniste; Florica Doroftei; Milan Masar; Pavol Suly; Veaceslav Ursaki; Barbora Hanulikova; Tomas Sopik; Vladimir Sedlarik; Ivo Kuritka; et al. (Heliyon)
The escalating global problem of antibiotic contamination in wastewater demands innovative and sustainable remediation technologies. This paper presents a highly efficient photocatalytic material for water purification: a three-dimensional ultra-porous structure of interconnected GaN hollow microtetrapods (aero-GaN), its performance being further enhanced by noble metal nanodot functionalization. This novel aero-nanomaterial achieves more than 90 % of tetracycline degradation within 120 min under UV and solar irradiation, demonstrating its effectiveness in both static and dynamic flow conditions, with the potential for reuse and recyclability. The higher surface area and chemical stability of the 3D aero-GaN architecture, compared to analogous ZnO structures, establish its significant potential for advanced water treatment applications and filter technologies.